Arabidopsis seedlings display a remarkable resilience under severe mineral starvation using their metabolic plasticity to remain self‐sufficient for weeks. (30th April 2019) - Réthoré, Elise; d'Andrea, Sabine; Benamar, Abdelilah; Cukier, Caroline; Tolleter, Dimitri; Limami, Anis M.; Avelange‐Macherel, Marie‐Hélène; Macherel, David
Summary: During the life cycle of plants, seedlings are considered vulnerable because they are at the interface between the highly stress tolerant seed embryos and the established plant, and must develop rapidly, often in a challenging environment, with limited access to nutrients and light. Using a simple experimental system, whereby the seedling stage of Arabidopsis is considerably prolonged by nutrient starvation, we analysed the physiology and metabolism of seedlings maintained in such conditions up to 4 weeks. Although development was arrested at the cotyledon stage, there was no sign of senescence and seedlings remained viable for weeks, yielding normal plants after transplantation. Photosynthetic activity compensated for respiratory carbon losses, and energy dissipation by photorespiration and alternative oxidase appeared important. Photosynthates were essentially stored as organic acids, while the pool of free amino acids remained stable. Seedlings lost the capacity to store lipids in cytosolic lipid droplets, but developed large plastoglobuli. Arabidopsis seedlings arrested in their development because of mineral starvation displayed therefore a remarkable resilience, using their metabolic and physiological plasticity to maintain a steady state for weeks, allowing resumption of development when favourable conditions ensue. Significance Statement: Although the seedling stage is considered as most hazardous in the life cycle of plants, we show that Arabidopsis seedlings that are arrested in their development because of mineral starvation remained fully viable for several weeks. These plants take advantage of energy dissipating mechanisms and flexibility in carbon storage to maintain a metabolic steady state, until conditions improve and allow the resumption of growth and development.